Pengaruh Kontrol Diri Dan Kecerdasan Emosional Terhadap Kinerja Pegawai ASN Satuan Polisi Pamong Praja Kabupaten Karawang - Destriani Nanda Amelia; Sari Marliani; July Yuliawati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the influence of self-control and emotional intelligence on the performance of civil servant employees (ASN) at the Civil Service Police Unit (Satpol PP) in Karawang. Using a descriptive, quantitative, and verificative approach, the research involved 103 employees as both the population and sample, with data collected through questionnaires and interviews and analyzed using path analysis with SPSS. The findings indicate that self-control obtained a total score of 4,414 with an average of 441, categorized as